Fabry Disease in Families With Hypertrophic Cardiomyopathy: Clinical Manifestations in the Classic and Later-Onset Phenotypes. (August 2017) - Adalsteinsdottir, Berglind; Palsson, Runolfur; Desnick, Robert J.; Gardarsdottir, Marianna; Teekakirikul, Polakit; Maron, Martin; Appelbaum, Evan; Neisius, Ulf; Maron, Barry J.; Burke, Michael A.; Chen, Brenden; Pagant, Silvere; et al.
Abstract : Background—: The screening of Icelandic patients clinically diagnosed with hypertrophic cardiomyopathy resulted in identification of 8 individuals from 2 families with X-linked Fabry disease (FD) caused by GLA (α-galactosidase A gene) mutations encoding p.D322E (family A) or p.I232T (family B). Methods and Results—: Familial screening of at-risk relatives identified mutations in 16 family A members (8 men and 8 heterozygotes) and 25 family B members (10 men and 15 heterozygotes). Clinical assessments, α-galactosidase A (α-GalA) activities, glycosphingolipid substrate levels, and in vitro mutation expression were used to categorize p.D322E as a classic FD mutation and p.I232T as a later-onset FD mutation. In vitro expression revealed that p.D322E and p.I232T had α-GalA activities of 1.4% and 14.9% of the mean wild-type activity, respectively. Family A men had markedly decreased α-GalA activity and childhood-onset classic manifestations, except for angiokeratoma and cornea verticillata. Family B men had residual α-GalA activity and developed FD manifestations in adulthood. Despite these differences, all family A and family B men >30 years of age had left ventricular hypertrophy, which was mainly asymmetrical, and had similar late gadolinium enhancement patterns. Ischemic stroke and severe white matter lesions were more frequent among family A men, but neither family A nor family B men had overt renal disease. Family A and family B heterozygotes had less severe or no clinical manifestations. Conclusions—: Men with classic or later-onset FD caused by GLA missense mutations developed prominent and similar cardiovascular disease at similar ages, despite markedly different α-GalA activities. Abstract : Supplemental Digital Content is available in the text.